Seed Germination of Three Milk Thistle (Silybum marianum (L.) Gaertn.) Populations of Greek Origin: Temperature, Duration, and Storage Conditions Effects - Vasiliki Liava; Georgia Ntatsi; Anestis Karkanis (Plants, 2023)
Milk thistle besides being a highly competitive weed is cultivated as a medicinal plant, and the seeds of which have been clinically utilized in several disorders caused in liver. The present study aims to evaluate the effect of duration and storage conditions, population, and temperature on seed germination. The experiment was conducted in Petri dishes with three replications and three factors: (a) wild populations of milk thistle (Palaionterveno, Mesopotamia, and Spata) originating from Greece, (b) duration and storage conditions (5 months at room temperature, 17 months at room temperature, and 29 months in the freezer at −18 °C), and (c) temperature (5 °C, 10 °C, 15 °C, 20 °C, 25 °C, and 30 °C). All three factors significantly affected germination percentage (GP), mean germination time (MGT), germination index (GI), radicle length (RL), and hypocotyl length (HL) and significant interactions among the treatments were noted. In specific, no seed germination was recorded at 5 °C, while the populations showed higher GP and GI at 20 °C and 25 °C after 5 months of storage. Prolonged storage negatively affected seed germination although, cold storage mitigated this effect. Moreover, higher temperatures reduced MGT and increased RL and HL with the populations reacting differently in storage and temperature regimes. The results of this study should be taken into consideration when proposing the appropriate sowing date and storage conditions of the seeds used as propagation material for crop establishment. Moreover, the effects of low temperatures such as 5 °C or 10 °C on seed germination as well as the high decline rate in germination percentage over time could be utilized in the design of integrated weed management systems thereby indicating the importance of the sowing time and the suitable crop rotation system to weed control.